Development of learning videos through the problem-based learning model to improve learning outcomes and creativity of Grade V students - Fajar Solidman Larosa; A. Asmin; Wildansyah Lubis (Inovasi Kurikulum, 2024)
This study assessed the feasibility and effectiveness of developing Problem-Based Learning (PBL) learning videos related to fractional lesson content for fifth-grade students at SDN 101764 Bandar Klippa. This research is related to implementing the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) in the research and development of learning videos. This study involved twenty-five students in Class V of SDN 101764 Bandar Klippa. The instruments used by researchers for data acquisition include observation, interviews, validation questionnaires, and tests. The developed Problem-Based Learning model is validated by expert validators based on the findings of learning research videos. From the results of the validity test by validators, the percentage of material expert eligibility of 95.2 percent of the criteria is very valid, the design expert's feasibility percentage of 96.19 percent is considered very valid, the media expert produces a validity level of 90 percent of the very valid criteria. The small group trial resulted in an efficient criteria percentage of 89.89 percent. The percentage of practicality of field test results of 91.48 percent is an efficient criterion. Effectiveness was achieved at the field trial stage, with 22 students (approximately 88 percent) passing the post-test. A gain score of 0.615 meets the criteria of moderate effectiveness. Based on empirical observations that show an increase in learning outcomes by 84 percent and an increase in student creativity by 100 percent, it is determined that Problem-Based Learning learning videos can effectively perfect the mathematics curriculum of grade V students of SDN 101764 Bandar Klippa. AbstrakTujuan penelitian ini adalah untuk menilai kelayakan dan efektivitas pengembangan video pembelajaran berbasis Problem Based Learning (PBL) yang berkaitan dengan isi pelajaran pecahan untuk peserta didik kelas lima di SDN 101764 Bandar Klippa. Penelitian ini berkaitan dengan implementasi model pengembangan ADDIE (Analysis, Design, Development, Implementation, Evaluation) dalam konteks penelitian dan pengembangan video pembelajaran. Penelitian ini melibatkan dua puluh lima peserta didik yang terdaftar di Kelas V SDN 101764 Bandar Klippa. Instrumen yang digunakan peneliti untuk perolehan data meliputi observasi, wawancara, angket validasi, dan tes. Model Problem Based Learning yang dikembangkan divalidasi oleh validator ahli berdasarkan temuan video penelitian pembelajaran. Dari hasil uji validitas oleh validator persentase kelayakan ahli materi sebesar 95,2 persen kriteria sangat valid, ahli desain persentase kelayakan sebesar 96,19 persen dinilai sangat valid, ahli media menghasilkan tingkat validitas 90 persen kriteria sangat valid. Hasil uji coba kelompok kecil menghasilkan persentase kriteria sangat praktis sebesar 89,89 persen. Persentase kepraktisan hasil uji lapangan sebesar 91,48 persen merupakan kriteria sangat praktis. Efektivitas dicapai pada tahap uji coba lapangan dengan 22 peserta didik (sekitar 88 persen) yang lulus post-test; skor gain sebesar 0,615 memenuhi kriteria efektivitas sedang. Berdasarkan observasi empiris yang menunjukkan adanya peningkatan hasil belajar sebesar 84 persen dan peningkatan kreativitas peserta didik sebesar 100 persen, ditetapkan bahwa video pembelajaran Problem Based Learning dapat menjadi sarana yang efektif untuk menyempurnakan kurikulum matematika peserta didik kelas V SDN 101764 Bandar Klippa.Kata Kunci: hasil belajar; kreativitas; pembelajaran berbasis masalah; video pembelajaran